DEVELOPMENT OF RISK FACTORS AND CLINICAL MANIFESTATIONS OF EXOGENOUS ALLERGIC ALVEOLITIS IN THE POPULATION OF THE REPUBLIC OF TAJIKISTAN - N.I. MUSTAFAKULOVA; A.I. SULTANOV; D.YU. ABDULLAEVA (Avicenna Tajik State Medical University, 2017)
Objective: To study the development of risk factors and specific features of clinical manifestations of exogenous allergic alveolitis (EAA) in the population of the Republic of Tajikistan. Methods: 100 patients with EAA aged from 17 to 67 years were examined. All patients are divided into 3 groups: I group (n = 35) with acute, II group (n = 30) with sub-acute and III group (n = 35) with the chronic course of the disease. Results: Most of the patients with EAA admitted to the hospital in the summer and autumn, and a smaller - in the spring and winter. EAA reasons were: Mycoplasma pneumonia, hay, cotton and grain dust. There were pneumonia-like, asthmoid and fibrosing variants of EAA. Conclusion: The clinical picture of EAA varied depending on the cause, variant and seasonality. Differences were observed in the expression of X-ray data.